Environmental Accounting Disclosure Practices: A Bibliometric and Systematic Review - Shoeb, Mohd; Aslam, Aamir; Aslam, Anam (International Journal of Energy Economics and Policy, 2022)
The aim of this study is to examine the importance of Environmental Accounting Disclosure Practices (EADP) and provide a systematic review based on the existing literature. Bibliometric analysis technique was used in this research work based on the Scopus database over a 30-year period (1991-2021), using a sample of 190 articles we determined the most relevant journals, influential authors, countries, keywords, academic institutions, most cited papers, and trends. The results of the study show that this area of research is still at an early stage but is developing at a greater pace. The current analysis reveals that there is a steady rise in publications, and major academic work in this area was from Italy, the USA and the UK. This research also highlighted that environmental accounting disclosure practices have a positive effect on a firm’s performance and that these disclosure practices are significantly dependent upon the firm’s characteristics such as firm size, profitability, time of listing, financial leverage, board size and firm age. This research work does not consider books and chapters but only includes papers published in academics and international journals. Future researchers can also take into consideration other literature review techniques and various other database platforms for data extraction.